Effect of iron content on the catalytic properties of activated carbon-supported magnetite derived from biomass - Lima, Sirlene B. (2013)
In recent times, the intense human activity has led to an increase of the agriculture wastes in the environment. "In order to find new applications for these materials, the effect of iron content (2.5, 5, 10 and 15%) on the catalytic properties of activated carbon-supported iron oxide, prepared from coconut shells, was studied. The iron amount affected the textural and reducing properties of the solids and particle sizes. Hematite was found for the most iron-poor sample, while particles of magnetite with a core of hematite were found for the others. These catalysts were effective in the methylene blue removal from aqueous solutions by adsorption and Fenton reaction. The solid with 15% of iron was the most active one probably due to the highest iron amount on the surface. These catalysts are environmentally friendly, contributing to the decrease of the solid wastes in the environment as well as to purify textile effluents, preserving water resources.